Tetra-arylborate lipophilic anions as targeting groups. Issue 25 (26th February 2021) - Gaddale Devanna, Kishore K.; Gawel, Justyna M.; Prime, Tracy A.; Cvetko, Filip; Benincá, Cristiane; Caldwell, Stuart T.; Negoda, Alexander; Harrison, Andrew; James, Andrew M.; Pavlov, Evgeny V.; Murphy, Michael P.; Hartley, Richard C.
Abstract : TPB lipophilic anions deliver cargoes to lysosomes and are excluded from mitochondria. Abstract : Tetraphenylborate (TPB) anions traverse membranes but are excluded from mitochondria by the membrane potential (Δ ψ ). TPB-conjugates also distributed across membranes in response to Δ ψ, but surprisingly, they rapidly entered cells. They accumulated within lysosomes following endocystosis. This pH-independent targeting of lysosomes makes possible new classes of probe and bioactive molecules.